Consumer Protection Against the Production and Distribution of Traditional Liquor - Martinoadi Batara; Edith Ratna Wahyuningrum (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Article 28 H, paragraph 1, of the 1945 Constitution of the Republic of Indonesia states: Everyone has the right to exist in physical and spiritual prosperity, to have a home and a good living environment, and to receive health care. Article 4 paragraphs (3) and (4) of Presidential Regulation No. 74 of 2013 on the Control and Supervision of Alcoholic Beverages state that alcoholic beverages may only be turned off after obtaining a distribution permit from the Food and Drug Supervisory Agency and can only be issued by business actors who already have a license to trade alcoholic beverages according to the regulated classification. The state ensures the safety of consumers and the preservation of their health when consuming traditional alcoholic beverages through Law No. 8 of 1999 concerning Consumer preservation. Because the distribution of alcoholic beverages in society must be of concern, as this condition is inversely proportional to the actual situation on the ground, as alcoholic consumers continue to experience health issues. Traditional liquor's impact on the market necessitates clear and firm regulations to ensure that these products satisfy the health and safety standards established by laws and regulations.